Prevalance and Risk Factors of Hyperemesis Gravidarum: A Retrospective Study (Medico Legal Update, 2020)
A Retrospective study was conducted to assess the prevalence and risk factors of hyperemesis gravidarumamong antenatal mothers in a selected tertiary care hospital, Kelambakkam, Kanchipuram District,Tamil Nadu, India. The objectives were to assess the prevalence and risk factors of hyperemesis gravidarumamong antenatal mothers by collecting the data from the medical records of the patients and to find theassociation between risk factors of hyperemesis gravidarum with the selected demographic variables amongpatients with hyperemesis gravidarum. The literature review was done and organized under various aspectson studies related to prevalence and risk factors of hyperemesis gravidarum among antenatal mothers withhyperemesis gravidarum. The research approach used for the study was quantitative research approach andthe design was retrospective design, 47 samples were participated in the study by using convenient samplingtechnique. Demographic variables are assessed by using the statistical measurement, prevalence and riskfactors of hyperemesis gravidarum among antenatal mothers with hyperemesis gravidarum. The levelof significance selected was p